Concept of climate-charged airspaces: a potential policy instrument for internalizing aviation's climate impact of non-CO2 effects. (14th September 2021) - Niklaß, Malte; Grewe, Volker; Gollnick, Volker; Dahlmann, Katrin
ABSTRACT: Approximately 50–75% of aviation's climate impact is caused by non-CO2 effects, like the production of ozone and the formation of contrail cirrus clouds, which can be effectively prevented by re-routing flights around highly climate-sensitive areas. Here, we discuss options how to incentivize re-routing approaches and apply multicriteria trajectory optimizations to demonstrate the feasibility of the concept of climate-charged airspaces (CCAs). We show that although climate-optimized re-routing results in slightly longer flight times, increased fuel consumption and higher operating costs, it is more climate-friendly compared to a cost-optimized routing. In accordance to other studies, we find that the averaged temperature response over 100 years (ATR 100 ) of a single flight can be reduced by up to 40%. However, if mitigation efforts are associated with a direct increase in costs, there is a need for climate policies. To address the lack of incentivizing airlines to internalize their climate costs, this study focuses on the CCA concept, which imposes a climate charge on airlines when operating in highly climate-sensitive areas. If CCAs are (partly) bypassed, both climate impact and operating costs of a flight can be reduced: a more climate-friendly routing becomes economically attractive. For an exemplary North-Atlantic network, CCAs create a financial incentive for climate mitigation, achieving on average more than 90% of the climate impact reduction potential of climate-optimized trajectories (theoretical maximum, benchmark). Key policy insights Existing climate policies for aviation do not address non- C O 2 effects, which are very sensitive to the location and the timing of the emission. By imposing a temporary climate charge for airlines that operate in highly climate-sensitive regions, the trade-off between economic viability and environmental compatibility could be resolved: Climate impact mitigation of non- C O 2 effects coincides with cutting costs. To ensure easy planning and verification, climate charges are calculated analogously to en-route and terminal charges. For climate mitigation it is therefore neither necessary to monitor emissions ( C O 2, N O x, etc.) nor to integrate complex non- C O 2 effects into flight planning procedures of airlines. Its implementation is feasible and effective.